Enhancing phase change thermal energy storage material properties prediction with digital technologies - Minghao Yu; Jing Liu; Cheng Chen; Mingyue Li (Frontiers in Materials)
IntroductionIn the field of materials science, the prediction of material properties plays a critical role in designing new materials and optimizing existing ones. Traditional experimental approaches, while effective, are resource-intensive and time-consuming, often requiring extensive trial-and-error methods. To address these limitations, the integration of digital technologies, such as computational modeling and machine learning (ML), has become increasingly important.MethodsThis paper proposes a hybrid multiscale modeling framework that integrates molecular dynamics (MD) simulations, finite element methods (FEM) from continuum mechanics, and supervised ML algorithms—including deep neural networks and gradient boosting regressors—to enable accurate and efficient prediction of material properties across scales. The method integrates MD simulations for atomic-level interactions using Lennard-Jones and embedded-atom method (EAM) potentials, FEM-based continuum mechanics for stress-strain analysis and thermal response evaluation, and ML techniques trained on multiscale descriptors (e.g., bond energy, stress tensor, coordination number) to model nonlinear property relations and accelerate design iteration. Hierarchical feature fusion modules combine low-level atomistic descriptors with high-level continuum features.ResultsBenchmark evaluations show improved performance in predicting elastic modulus, thermal conductivity, and phase transition temperature across five material classes. Our experimental results demonstrate that this integrated methodology outperforms conventional methods in both prediction speed and accuracy, particularly in complex or multicomponent systems.DiscussionThis approach significantly reduces computational costs and accelerates material design workflows by predicting properties with high precision across a wide range of materials. It aligns with current trends in leveraging advanced digital technologies to enhance materials discovery, offering a robust, scalable, and extensible framework for the optimization and design of advanced materials in various industrial, technological, and scientific applications.